Salvando distancias - Pastor, Álvaro, 1972- (Nephilim Producciones, S.L., 2014)
Learning is a journey that lasts a lifetime. Falling down and getting back up. We are not all that different even though an ocean lies between us. Sometimes, distances are not measured in kilometres.--